An unusual unplanned complex suicide by arm cutting, poisoning, and self-immolation - Claudio Terranova; Luca Massaro; Francesco Angiola (Forensic Science International: Reports, 2023)
Different methods of suicide, when combined with contamination of the scene, increase the difficulty of interpreting the dynamics of an event. In the presented case, the discovery of a corpse with widespread burns, singed hair, an “X”-shaped cut on the arm with a weapon distant from the body, and the death scene significantly altered by subjects with psychiatric disorders raised the hypothesis of murder in the initial phase. However, the integration of the death scene investigation with medicolegal, toxicological, and radiological analyses allowed for the identification of an unusual unplanned complex suicide by arm cutting, poisoning, and self-immolation.